Acute effect of speed test on the skin temperature of elite soccer players - Pinheiro, A. M.; Tuono, A. T.; Vieira, N. A.; de Rezende, T. M.; Borin, S. H.; Hartz, C. S.; Padovani, C. R.; Torres, F. C.; Borin, J. P. (Revista Brasileira de Medicina do Esporte, 2021)
Introduction: Infrared thermography has been used in several areas, mainly in sports training, and specifically in soccer. Objectives: The objectives of the study were to verify the acute effect of a displacement speed test on the skin temperature of elite female soccer players, to observe pre- and post-test thermal asymmetries, and to compare responses in the anterior and posterior regions of lower limbs. Methods: Cross-sectional study that evaluated 17 soccer players of the 2018 Brazilian Championship. They were submitted to thermography before and 10 minutes after performing the displacement speed test. Thermographic images were collected using a FLIR® model 8 thermal imager and changes in skin temperature in the anterior and posterior regions of the lower limbs were analyzed, according to the areas of interest. Descriptive statistics were performed and mean and standard deviation of the temperatures of the areas of interest were analyzed. The normality of the data was verified, and then the Student`s t test for normal paired and independent samples and the Mann-Whitney test for non-normal samples were conducted, with p <0.05 being adopted for significance level. Results: It was possible to observe that after the test there was an increase in skin temperature in all the regions analyzed, both on the dominant and non-dominant sides (p <0.05). Regarding the analysis of the anterior region, it was possible to observe a higher temperature (p <0.05) in the region of the tibial muscles than in the region of the quadriceps muscles. Conclusion: It is concluded that thermography helps to understand the thermal responses of lower limbs after applying the displacement speed test. The study shows that thermographic evaluation can guide the organization of the training session when motor tests have previously been applied, and in the detection of abnormal overloads, helping to prevent injuries.